Teaching attentive listening to medical students: need and strategies - Nawaz, Zerlis; Mahboob, Usman (Journal of the Pakistan Medical Association, 2023)
Listening is a primary skill essential for learning and is positively correlated with academic achievement. It also enables a healthcare professional to fully explore patients' concerns in healthcare settings. There has been much discussion on how effective listening practices can facilitate students’ learning. A clear understanding of listening as a ‘process’ and planned listening activities can help exploit listening skills in formal and informal learning contexts. This paper explores strategies through which listening can be taught to undergraduate medical students in a small group setting. A planned tutorial is discussed, including methods that can be used to teach listening skills. The simple guidelines provided here can be used in most small group teaching methods. These teaching strategies are likely to allow undergraduate students to evolve into better listeners and, therefore, better lifelong learners and future physicians. Keywords: Medical students, Active listening skills, Teaching Methods, Small group teaching.